PERCUTANEOUS INTERVENTION IN STABLE ANGINA: WHAT ISSUES DO WE SOLVE? - Yu. A. Karpov; I. L. Kozlovskaya; O. S. Bulkina; V. V. Lopukhova (Российский кардиологический журнал, 2018)
In the article, a role of percutaneous intervention discussed in stable ischemic disease of the heart, and an evolution presented of the perspectives on its influence on prognosis and clinical presentation of the disease. The results provided, of recent trials, including the ORBITA. According to current clinical guidelines, endovascular treatment does improve prognosis in patients with the left coronary artery stem lesion and proximal left descending artery lesion, as in a significant area of damaged myocardium involved in temporary ischemia. Percutaneous coronary intervention should be done in patients with continued clinical presentation of angina and nonsatisfactory life quality regardless the optimal medication treatment.